Climate change, natural disasters, and international migration: A country-level analysis considering climatic zones - Martínez-Zarzoso, Inma; Nowak-Lehmann, Felicitas; Paschoaleto, Rafael Duarte Lisboa (Frontiers in Climate, 2023)
This paper investigates the link between climatic events and bilateral migration from countries in the Global South to OECD countries. A gravity model is estimated using panel data techniques and bearing in mind potential sources of heterogeneity across subsamples. The main novelty is to distinguish by climatic zones, while also considering commonly used social and economic stresses, such as income levels and incidence of conflict. The analysis is based on bilateral emigration flows from 76 developing countries to OECD countries in the last decades. The results show that increasing extreme temperatures and storms in arid and semi-arid zones act as triggers of bilateral migration from South to North and that the estimated effects are non-negligible. The results are robust to a battery of tests, including dividing the sample according to the levels of conflict and poverty.